PENINGKATAN PEMAHAMAN URGENSI KONSERVASI SUMBER DAYA AIR KEPADA GURU DAN MURID SMAIT ATTAUHID BABELAN - Evita, Liza; Umardani, Mohamad Kharis; Mahmud, Amir (LPPM Universitas Flores, 2024)
This activity aims to provide a fundamental understanding of the importance of water resource conservation in supporting the availability of water in sufficient quantity and quality to meet the needs of humans and other living things, both now and in the future. Partners in this activity are: SMAIT Attauhid, Babelan, and Bekasi Regency. Problems faced by partners: (1) limited access to legal information about the urgency of water resources conservation (2) lack of insight into legal knowledge of partner actors related to water resources management regulations. Solutions are offered by providing education about the importance of water resources conservation. This legal counselling activity is carried out using the participatory action method supported by lecture and discussion methods. Activities have been carried out well, with the result that there has been an increase in awareness and understanding of the importance of water resources conservation, goals and principles of water resources management, community rights and obligations in water resources management, seen from before and after the implementation of legal counselling activities on the urgency of water resources conservation.